목재를 이용한 큐브위성 개발동향 - 조우민(Woo-Min Cho); 이유선(Yu-Sun Lee); 오현웅(Hyun-Ung Oh) (항공우주시스템공학회지, 2024)
With increasing demand for small satellites for constellation missions and very low earth orbit operations recently, satellite technology development is focusing on being smaller and lighter. In addition, the number of satellites launched each year is increasing as launch costs are reduced by using reusable launch vehicles and simultaneous launches using multiple payload adapters. As a result, satellites decommissioned at the end of their missions contribute significantly to the accumulation of space debris. Effective reduction and disposal strategies are urgently needed internationally. Space debris can collide with operational satellites, causing mission failure. Debris from serial destruction can cause problems in the orbital environment. Wood, a biodegradable material, is attracting attention as a new material for satellite structure to replace metallic materials. WoodSat can be self-destructed by on-orbit incineration after the end of a mission. It has lighter weight, better processability, and lower manufacturing cost than conventional materials. Research is underway to validate the suitability of wood as a space material, with additional launch and orbital environmental test. This paper presents the development trend of satellites using wood and considers the possibility of satellite applications. 근래 군집임무, 초저궤도 운용을 위한 (초)소형위성의 수요가 증가함에 따라 위성 기술 개발이 소형화, 경량화에 집중되고 있다. 또한, 재사용 발사체로 인한 발사비용 절감과 다중탑재시스템 활용으로 동시다발적 발사가 가능해지면서, 매년 우주를 향한 위성의 수는 증가하고 있다. 이로 인해, 임무 종료 후 폐기되는 위성이 다량의 우주쓰레기로 파생되어 경감 및 처리 방안이 국제적인 관심사로 대두되는 상황이다. 우주쓰레기는 운용 중인 위성과 충돌하여 임무 실패를 야기하고, 연쇄적 파괴로 생성된 파편은 궤도환경 악화 문제를 발생시킨다. 전술한 문제점의 해결책으로 기존 금속 재료를 대체할 새로운 위성제작 소재로 생분해성 물질인 목재가 주목받고 있다. 목재 위성은 임무 종료 후 궤도 소각을 통한 자폐 폐기절차 수립이 가능하고, 기존 소재 대비 경량화, 가공성 향상, 제작 비용 절감의 이점들을 동반한다. 해외에서는 목재의 우주급 소재 이용 적합성을 검증하기 위한 연구가 활발히 진행되고 있으며, 추가로 발사환경시험, 궤도환경시험을 수행하고 있다. 본 논문에서는 목재를 이용한 위성 개발동향을 소개하고, 향후 위성 적용 가능성을 고찰하고자 한다.